2017
DOI: 10.1002/elps.201600548
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetically controlled fluid injection into unicellular microalgae

Abstract: Electrokinetically controlled microinjection is reported as an effective transport mechanism for microinjection into the wild-type strain of the widely studied model microalga Chlamydomonas reinhardtii. A microinjection system using glass capillary pipettes was developed to capture and impale the motile cells. To apply an electric field and induce electrokinetic flow (e.g., electrophoresis and electroosmosis), an electrode was inserted directly into the solution inside the impaling injection pipette and anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…For C. reinhardtii cells, immediate cell rupture upon impalement have been reported for needles with tips that are larger than 900 nm . We have also found that complete skewering of the C. reinhardtii induce immediate cell death, and when the needle density is too high ( e. g . 10 8 needles per cm 2 ), the cells rest on top of the needles (without being impaled) due to the “bed of nails” effect .…”
Section: Template Synthesis Of Nna For C Reinhardtii Impalement and supporting
confidence: 64%
See 2 more Smart Citations
“…For C. reinhardtii cells, immediate cell rupture upon impalement have been reported for needles with tips that are larger than 900 nm . We have also found that complete skewering of the C. reinhardtii induce immediate cell death, and when the needle density is too high ( e. g . 10 8 needles per cm 2 ), the cells rest on top of the needles (without being impaled) due to the “bed of nails” effect .…”
Section: Template Synthesis Of Nna For C Reinhardtii Impalement and supporting
confidence: 64%
“…We have shown through similar assays that CC124 cells retain viability after impalement and injection by a hollow glass‐capillary needle . However, further studies are needed to assess the impact of hollow Pt/Ni NNA impalement on cell viability.…”
Section: Impaling C Reinhardtii With Nnamentioning
confidence: 70%
See 1 more Smart Citation
“…Other methods include stable nuclear transformation systems for Pleurochrysis carterae using polyethylene glycol (PEG)-mediated transfer of hygromycin B-resistance genes [ 85 ]. Recent reports present genetic transformation of microalgae by bacterial conjugation [ 86 , 87 ] and gene injection [ 88 ]. In addition to these techniques, other emerging methods, such as cell-penetrating peptides, nanoparticles, metal–organic frameworks, and liposomes, have not yet been demonstrated in microalgae [ 12 , 89 , 90 , 91 ].…”
Section: Genetic Engineering Transformation Methods For Biopharmaceut...mentioning
confidence: 99%
“…To achieve subsequent mechanical intracellular delivery to captured single cells, , negative pressure is generally combined with a microfluidic chip to trap single cells. ,, However, this method suffers from randomness in the intracellular delivery location after cell capture. A micropipet-based method was used to capture small-size suspended single cells of plants and carry out intracellular delivery, in which the holding pipet used has a sharp and thin-wall tip opening . Plant cells have cell walls, while animal cells do not.…”
mentioning
confidence: 99%